Economic aspects of the development of the South African wine industry in the twentieth century - Venturas, D A E (School of Economics, 2016)
This study was conducted in order to describe and explain certain economic aspects of the development of the South African wine industry during the twentieth century. A brief historical background is given to place this development into perspective and to give some idea of the way in which the foundations of South African viticulture were laid. One of the main points emerging from a study of the early years of South African viticulture is that the quality of the wines and brandy produced, at the turn of the century, was low and far inferior to that of European wines and brandy. This, as well as restrictions on the sale and distribution of liquor through licensing legislation, tended to limit the potential market for South African wine products, so that an uneasy and unstable relationship developed between supply and demand.